2002
DOI: 10.1055/s-2002-20107
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Bildqualität, Hochkontrastauflösung und Dosis am Stamm- und Gliedmaßenskelett mit einem neuen dedizierten CT-System (ISO-C-3D)

Abstract: Preliminary results show, that image quality of C-arm-based CT-imaging (ISO-C-3D) seems to be adequate in smaller joints. ISO-C-3D images of the hip and axial skeleton show a decreased image quality, which does not seem to be sufficient for diagnosing subtle fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 10 publications
0
9
0
6
Order By: Relevance
“…Preclinical studies carried out on cadaveric specimens and on the high-contrast phantom showed sufficient image quality for the axial skeleton [21]. Although 3D image intensifiers have been used clinically for almost a decade, only a few studies are available that examine the diagnostic value of intraoperative 3D imaging in spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies carried out on cadaveric specimens and on the high-contrast phantom showed sufficient image quality for the axial skeleton [21]. Although 3D image intensifiers have been used clinically for almost a decade, only a few studies are available that examine the diagnostic value of intraoperative 3D imaging in spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison of the individual patient radiation dose parameters is not possible because of the total different application forms of x-radiation. Dose measurement at phantoms showed a considerable lower radiation exposure of the lumbar spine using 3D intensifier compared with a spiral CT standard procedure [21]. Berger et al confirmed the lower radiation doses using the Ziehm Vario 3D intensifier [3].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported when a series of images of the axial skeleton and limbs were created with an ISO-C-3D fluoroscopy device. 17,18 A comparison between fpVCT or fpDVT scans of isolated temporal bone specimens and the scans of whole-head specimens revealed that the detailed resolution of the images was higher; however, with flat panel scanners, the filigree structures of temporal bone were displayed more clearly. The images of the whole-head specimen on flat panel devices were noisier.…”
Section: Figmentioning
confidence: 99%
“…Auch an Wirbelsäule (Pedikelschrauben) und Becken (Sakrum, Sakroiliakalgelenk, Azetabulum) ist die 3D-Bildgebung möglich und sinnvoll.Allerdings sind dazu Operationstische oder Zubehör aus röntgendurch-lässigem Material erforderlich. Die Strahlenbelastung ist für die Extremitätendarstellung vergleichbar mit der einer CT-Untersuchung, für Rumpfabschnitte etwas höher [6].Zu beachten ist die Streustrahlung [6], die während der Bildaquisition für die 3D-Rekonstruktion -im Gegensatz zur bisherigen C-BogenDurchleuchtung -durch Einhalten eines Sicherheitsabstands von 3,50 m vermieden werden kann.…”
Section: Diskussionunclassified